Omsk hemorrhagic fever virus: review of the biology, ecology, and disease associated with a historic tick-borne pathogen - Nidhi P. Kumar; Matthew Hathaway; Matthew K. Demshuk; Taylor O. DeHaven; Stefania M. Farha; Angelena M. Donovan; Andrew J. Burdette; Gracie L. Walls; Kara M. Selesky; Dia C. Beachboard; Christopher C. Stobart; Haijuan Wang (​​​​​​​​Infectious Diseases & Immunity)
Abstract. Omsk hemorrhagic fever virus (OHFV) is a tick-borne flavivirus associated with acute febrile illness and hemorrhagic disease in humans. OHFV was first identified in 1947 and since its identification has largely remained endemic to the Omsk region of the Russian Federation, where it continues to result in illnesses each year. However, the 2 primary tick vectors of OHFV exhibit ranges that extend far beyond the Omsk region, and the recent positive confirmation of OHFV in samples outside of the historic endemic range, in both the Russian Federation and neighboring Kazakhstan, to the south raises new concerns about the future potential of the pathogen. In this review, we comprehensively discuss the emergence, virology, ecology, and disease of OHFV.